The survey of spatial disparity in India with the application of the SENTIENT Index - Wilhelm, Zoltán (Hungarian Geographical Bulletin, 2011)
Most of the articles writt en on India treat spatial disparity within the country at the level of the member states and union territories which is an imperfect approach. Reality is hidden behind the averages of the extremes. In this study the data of 593 districts of India were elaborated, based on the district level information of the census held in 2001. As a result the districts of India were classified by the relative level of development, using the so-called SENTIENT Index. The index of complex development that I created on the basis of the tetrahedron model sensitively “reacts” to the changes occurring in the geographical environment. It is modified as an effect of the events taking place in the individual spheres, so it can be a tool producing spectacular results of comparative spatial studies. The present paper explores the coherences of the spatial disparity within India and the internal correlations of the state of development or backwardness also become clear.